Challenges of laparoscopic radical nephrectomy at the upper limits of obesity - Peter Galloway; Berni Frost; Avi Raman (Urology Case Reports)
As worldwide obesity rates increase the number of patients with an elevated BMI requiring urological surgery will increase. Although obesity has previously been considered a relative contra-indication to laparoscopic surgery, here we present a case of successful laparoscopic nephrectomy performed due to renal cancer in a patient with a BMI >60 kg/m2 together with a review of the associated challenges.